“Shining Batu” : Sistem Informasi Wisata Dan Kuliner Kota Batu - Eka Sifatul Fitri; Ardania Safitri; Anggi Jihan Putri Rumadhan; Chusnatun Nisa' (Jurnal Ilmiah Informatika, 2019)
The government of Batu city provides the application called "Shining Batu" to make it easier for society from outside and inside of Batu city to obtain information. The purpose of this study is to provide integrated information in the "Shining Batu" application. The research methods used are qualitative and quantitative. Secondary data were obtained from agency reports and exploration of applications through smartphones. The results of the research application "Shining Batu" consists of some information that is integrated with the presentation of some information that are information about the description of tourist attractions and the nearest culinary places. Utilization in the "Shining Batu" application is monitored through a system that shows good benefits by reaching users outside the Batu City area.